Extreme devotion - Voice of the Martyrs (Organization) (Nashville, Tenn. : W Pub. Group, 2001)
This daily devotional features hundreds of stories of ancient to modern day believersmany of whose stories are published here for the first timewho sacrificed everything for Christ. Each true account concludes with a life application and a Bible verse to challenge you to live out your own extreme devotion.
Keywords: Persecution -- History -- Case studies; Evangelistic work -- History -- Case studies; Christian martyrs -- History -- Case studies; Christian martyrs; Evangelistic work; Persecution; Case studies; History